1989
DOI: 10.2331/suisan.55.605
|View full text |Cite
|
Sign up to set email alerts
|

The relative growth of Panulirus phyllosoma larvae in Japanese Waters.

Abstract: Examination of relative growth of cephalic shield length, cephalic shield width, thorax width and abdomen length to body length revealed the occurrence of six forms of Panulirus phyllosoma, five known and one undescribed, in Japanese waters. These forms were identified as follows: Oshima's form F, which has been proposed as P. japonicus, is identical with this species and includes P. longipes which has close affinity to P. japonicus. Murano's form C is identified as P. penicillatas. Murano's form D and the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the seas surrounding Japan, phyllosoma larvae regarded as P. longipes or P. japonicus have been collected by several workers. 32–35 Oshima reported two forms (forms E and F) of phyllosoma larvae of Panulirus . 32 Thereafter, Murano described five forms (forms A–E) of late‐stage Panulirus larvae.…”
Section: Discussionmentioning
confidence: 99%
“…In the seas surrounding Japan, phyllosoma larvae regarded as P. longipes or P. japonicus have been collected by several workers. 32–35 Oshima reported two forms (forms E and F) of phyllosoma larvae of Panulirus . 32 Thereafter, Murano described five forms (forms A–E) of late‐stage Panulirus larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Following Gurney's description (1936), Oshima (1942) reported that two Forms (E and F) occur in Japanese waters. Later, Murano (1971) observed five Forms (A to E) of late-stage phyllosoma larvae of Panulirus in waters adjacent to Japan and suggested his Form A corresponded to Oshima's Form F. Murano (1971), and subsequently Nonaka et al (1989) suggested that phyllosoma larvae of P. japonicus and P. longipes both belong to Form A, but exact species identification was not possible. Sekiguchi (1986) proposed that late stage phyllosoma larvae of P. japonicus and P. longipes can be discriminated by the ratio of cephalic shield and thorax widths.…”
Section: Introductionmentioning
confidence: 99%
“…In the Japanese spiny lobster, Panulirus japonicas (Decapoda, Palinuridae), rearing experiments in the laboratory have shown that metamorphosis to the post larval stage occurs between 231 and 417 days after hatching.2,3,4} However, this long larval life has not yet been proved in the ocean, because the number of captured wild phyllosoma larvae around Japan is not large and serial growth data on wild larvae have not yet been published Among 5 forms (A-E) of palinurid larvae captured around Japan,) Form A is thought to be P. japonicus. 6) Although 127 Form A larvae with body lengths exceeding 20 mm have been captured hitherto,) far fewer young stages smaller than 20 mm long have been caught, with the exception of new hatchlings s) Moreover, late-stage phyllosoma of the P. japonicas group may be morphologically similar 6,9) and Matsu da. and Yamakawar10) found no morphological differences between P. japonicas and P. longipes larvae reared in the laboratory.…”
mentioning
confidence: 99%